JUAL BELI SUKUK DI BURSA EFEK INDONESIA SURABAYA - Zainul Anwar; Subaidi; Subyanto Subyanto (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2022)
Sukuk was an investment instrument that provides opportunities for Muslim and non-Muslim investors to invest in Indonesia.It could be used to build the nation's economy and create society welfare. The facts showed that the market would be very responsive to the sukuk issuance. Almost all sukuk was issued, was absorbed by the market, even in some cases caused excess demand. The sale and purchase of sukuk on the Indonesia Stock Exchange was carried out in four processes, from the account opening and order submissionstage, the order processing stage, the transaction stage, and the clearing, guarantee and transaction settlement stages.They applied to all types of securities traded on the Indonesia Stock Exchange. The difference lies only in the specifications of transactions such as fractions and price limits, which are carried out by educating the public about the process. While the form of transactions was carried out at securities trading places based on precautionary principles and sharia principles which refered to the fatwa of the National Sharia Board - Indonesian Ulema Council (DSN-MUI) and the Financial Services Authority (POJK) as the institution that oversees and regulates the process of the Sukuk transaction mechanism on the Indonesia Stock Exchange in Surabaya.